Analysis of Periodicity of the Electronic Devices' Serviceability State Inspection - Stupak, V. (Elektronika ir Elektrotechnika, 2005)
The restorable electronic devices are being analyzed. Their serviceability is periodically controlled with the help of built-in test equipment in the time intervals. А calculation method of periodicity of the serviceability state inspection is offered due to some peculiarities of the devices and their running costs. Analyzing periodicity of the serviceability state inspection, some running costs are being examined. Such costs are caused by the following expenses: maintenance, restoration of the state of serviceability, situational stoppage, non-effective usage and failure of the second type. The semi-marker stochastic process is supposed to be used in an exploitation model for description of the electronic devices’ changes. This method can used for calculating some other maintenance indexes - the rational number of serviceability state inspection within time between periodical tests and also the rational durations of time between periodical tests. Bibl.3 (in Lithuanian; summaries in Lithuanian, English and Russian).